Evaluasi Pelayanan Pengembangan Kompetensi di Kawasan Geodiversitas BRIN Karangsambung - Ahmad Saefuddin Manshur; Indra Riswadinata; Tri Kukuh Prasetiyo; Nurul Diniyati (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2023)
Evaluation is an essential part of forming optimal services according to the expectations and needs of users. This study aims to evaluate competency development services, including programs, organizers, and facilitators, so that people can know the quality of services received by users of competency development services at the BRIN Karangsambung Geodiversity Area. The results of this study help maintain, improve, and enhance services and become considerations for stakeholders. This study used a survey method with accidental sampling as the sampling technique. The evaluation results show that implementing competency development services at the BRIN Karangsambung Geodiversity Area is very good, with an overall average score of 3.70 on a scale of 4.00. Suggestions for improving services need to enhance coordination between service functions, consumption management, and the quality of lodging facilities.